PENGELOLAAN SAMPAH KERTAS DI INDONESIA - Sri Wahyono (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2001)
Paper waste is one type of municipal solid wastes that is not properly manage yet. It contributes about ten percent of MSW. Indonesia paper waste generation is about 1.6 million ton per year which 70 percent of them was recovered byscavengers and sold to the recycling paper industries. To optimize the paperwaste management, it is needed cooperation between community, private sectors and government in the MSW management. In this article, the author talks about paper waste generation and its potency, prospect and route of its market, and strategy of paper waste management.